Individual and personal qualities of bailiffs with various types of professional deformation - Ya. A. Korneeva; A. V. Korneeva; M. A. Tunkina; A. S. Yurieva (Acta Biomedica Scientifica, 2022)
Background. Insufficient knowledge of the professional deformation of bailiffs with the accumulated research material that reveals the essence of this phenomenon, as well as the need to take into account the specifics of the activity and individual and personal characteristics of this category of employees, determine the relevance of this study.The aim: to identify and describe the individual and personal qualities of bailiffs with various professional deformation types.Material and methods. In this work, the following research methods were used: the author’s questionnaire for assessing seven types of professional personal deformation; psychological testing of individual and personal qualities using methods regulated by departmental documents; statistical methods (descriptive statistics, two-stage cluster and correlation analyzes). The study involved 277 employees of the Federal Bailiff Service of the Arkhangelsk region.Results. Bailiffs showed such professional deformations as overcontrol, authoritarianism and conservatism. The interrelation of all professional deformation types severity with the individual and personal qualities of the bailiffs, which are among the professionally important qualities, has been established. At the same time, the insufficient expression of these qualities contributes to the professional deformation development. The only exceptions are the level of active communication and normativity, which, with excessive development, also contribute to the appearance of personality deformations and contribute to a decrease in the effectiveness of activities. Most types of character accentuations and their various combinations contribute to the professional deformation development of bailiffs, i. e., are her personality markers. Moderate severity of the dysthymic type of character accentuation reduces the likelihood of developing occupational deformity.Conclusion. Within the framework of the practical use of the results of this study, it is necessary, when conducting professional selection of personnel and periodic assessment of personnel, to pay attention to the level of expression of professionally important qualities that have a relationship with key types of professional deformation. This will allow timely implementation of measures to prevent the development of professional deformations of employees.